(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
In this study, the effect of different amounts of copper (CU) on the microstructure and mechanical properties of thixoformed Al-6Si-xCu-0.3Mg (x= 3, 4 and 5, mass fraction, %) were investigated. The alloys were prepared via cooling slope casting technique, before there were thixoformed using compression press. All of the alloys were then characterized using optical microscope (OM), scanning electron microscope (SEM) and energy dispersive X-ray (EDX). The results obtained revealed that cooling slope casting produced a non-dendritic microstructure and the intermetallic phase in the thixoformed samples was refined and evenly distributed. The results also revealed that as the Cu content in the alloy increases, the hardness and tensile strength of the thixoformed alloys also increase. The hardness of thixoformed Al-6Si-3Cu was 104.1 HV while the hardness of Al-6Si-5Cu alloy was increased to 118.2 HV. The ultimate tensile strength, yield strength and elongation to fracture of the thixoformed alloy which contained 3wt.% Cu were 241 MPa, 176 MPa and 3.2% respectively. The ultimate tensile strength, yield strength and elongation to fracture of the alloy that contained 6wt.% of Cu were 280 MPa, 238 MPa and 1.2% respectively. The fracture surface of the tensile sample with lower Cu content exhibited dimple rupture while higher Cu content showed a cleavage fracture.